ANALISIS PERAN BUKU TEKS BAHASA ARAB TERHADAP PEMAHAMAN SISWA KELAS VII MADRASAH TSANAWIYAH SWASTA MA’HAD AL-ZAYTUN - Nurul Azkiyah; Moch. Hasyim Fanirin; Iis Susiawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of the Arabic language textbook Semangat Mendalami Bahasa Arab for MTs Grade VII Volume 1 (Erlangga, 2023) in supporting the comprehension of seventh-grade students at Madrasah Tsanawiyah Swasta Ma’had Al-Zaytun in the 2024/2025 academic year. The textbook's role is examined in terms of its contribution to students' understanding of language skills (listening, speaking, reading, writing), influenced by factors such as comprehensible input and multimodal elements. This research used a qualitative descriptive approach. Data collection techniques included observation, interviews, documentation, and focus group discussions. Data were analyzed using data reduction, data display, and conclusion drawing. The findings show that the textbook significantly impacts students’ comprehension and motivation. Strengths include thematic content and illustrations, while weaknesses like unvocalized texts hinder independent learning. Teachers' adaptations (e.g., read-translate strategies) bridge gaps, aligning with the Merdeka Curriculum. The study recommends textbook revisions and teacher training to enhance accessibility and effectiveness. Keywords: Arabic textbook, student comprehension, comprehensible input, Merdeka Curriculum, madrasah tsanawiyah